PENGARUH ASUPAN PAKAN TERHADAP KADAR ALBUMIN DARAH PADA KAMBING KACANG JANTAN (Capra hircus) - , MUHAMMAD ABDUL LATHIEF ZAIN; , Dr. drh. Irkham Widiyono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The background of why the researcher conducting this research is because there are many goats in Indonesia that easily attacked by various deseases coming from the feed that is not given as needed. The objective of this research is to investigate the effect of feed intake in blood albumin on Kacang Goat (Capra hircus). Six healthy adult male goats (one year old) were used in this study. Those goats were cared in individual cages with size of 2 x 1m. The goats were divided into two groups, control group and restriction group. Before the period of investigation the goats were fed adlibitum. During the investigation period, control animals were fed adlibitum, but the animals in restriction group were fed at the level of 78% of its adlibitum feed consumption. Blood samples were collected from vena jugularis. Albumin in serum was determinated using SYNCHRON CX ® System(s). Mean difference between control and restriction group was analysed using t-Test. The results of this research showed the albumin level in a full feeding period was 3.78 ± 0.07 g/dl, while the albumin level at the end of the restriction period was significantly reduced to the level of 2.34 ± 0.11 g/dl (p<0.05). It can be concluded that feeding restriction for 7 weeks period result in a significant decrease of the albumin level in the Kacang goats.